2023
DOI: 10.1039/d2ra07514h
|View full text |Cite
|
Sign up to set email alerts
|

Thermal plasma processing of Moringa oleifera biochars: adsorbents for fluoride removal from water

Abstract: Moringa leaf biochar-based adsorption of fluoride in contaminated drinking water.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 45 publications
(54 reference statements)
0
3
0
Order By: Relevance
“…FESEM is the most versatile technique to observe a sample's surface morphology and was performed using the JEOL JSM‐7610F Plus model of scanning electron microscope (Gourai et al ., 2023).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…FESEM is the most versatile technique to observe a sample's surface morphology and was performed using the JEOL JSM‐7610F Plus model of scanning electron microscope (Gourai et al ., 2023).…”
Section: Methodsmentioning
confidence: 99%
“…Gold coating were added to the sample to provide electrical conductivity because it provides high‐resolution images of the metals. In EDS, the elemental analysis was performed using OXFORD EDS, which measured the intensity of the X‐ray signals generated by the electron beam when it struck the surface of the sample (Gourai et al ., 2023).…”
Section: Methodsmentioning
confidence: 99%
“…In recent years, several studies have reported on the potential of carbonaceous groups as a novel class of adsorption sites for uoride (Gourai, et al, 2023;Zhang and Jia, 2016b). The presence of hydrogen bonding and electrostatic attraction has been well-established, but Manna et al proposed that uoride can also form covalent bonds with carbon atoms during the adsorption process (Manna, et al, 2015).…”
Section: Introductionmentioning
confidence: 99%